Emotional organization and its relation to cognitive speed in kindergarten children (Journal of the College of Basic Education, 2020)
The aim of the present research is to identify the emotional organization and its relation to the cognitive speed among kindergarten children. Kindergartens (10) boys and girls from each kindergarten of the Directorate General of Education Baghdad Rusafa second and to achieve the objectives of research. Ismael 2009 Scale for emotional organization was developed to suit the kindergarten children which consists of (21) items distributed on two tasks and corrects the scale with a double balance (1, 0). The researcher adopted the Kakan test (kagan, 1971). The test consisted of (12) items and both tests are applied individually. After comparing the data statistically, it was found that the children of the sample enjoy the emotional organization. The correlation between emotional organization and cognitive speed shows a positive correlation between emotional organization and cognitive speed in kindergarten children